The Impact of ESG Program Implementation on Company Performance in the Hospital Sector of Companies Listed on the IDX in 2021–2024 - Indrawati Indrawati; Indri Kartika (Journal of Social Research, 2025)
Hospitals, as providers of public healthcare services, view ESG as crucial for business sustainability, survival under any circumstances, and gaining stakeholder trust. The implementation of environmental, social, and governance programs is increasingly under scrutiny in assessing company performance. This study will examine how environmental, social, and governance aspects will affect company performance in the hospital sector. The population of this study was hospital sector companies listed on the Indonesia Stock Exchange (IDX) in 2021–2024. The sampling method was purposive sampling, resulting in 10 research samples. Hypothesis testing was conducted using the Pls-Sem approach using the SmartPLS application to examine the relationship between variables. The results showed that environmental factors had a significant positive effect on company performance, social factors had a significant negative effect on company performance, and governance factors had a significant negative effect on company performance. This research can be expanded by using samples from other industries or adding moderating or mediating variables. Companies should comply with ESG regulations. Furthermore, the government can use the results of this study to improve ESG regulations.